The European archaeologist. 1-21A,, 1993-2004 - Cleere, Henry; Waugh, Karen; Samson, Ross (2014)
This volume gathers together the first 10 years of 'The European Archaeologist', from Winter 1993 through to the 10th Anniversary Conference Issue, published in 2004 for the Lyon Annual Meeting.